Microdochium sichuanense sp. nov. (Microdochiaceae, Xylariales), from a Poaceae host in Sichuan, China - Dissanayake, Lakmali S.; Kang, Ji-Chuan; Maharachchikumbura, Sajeewa S.n. (Phytotaxa, 2023)
During our investigation of ascomycetes fungi on Poaceae, a microdochium-like fungus was collected from dead grass leaves from a terrestrial habitat in Chengdu, Sichuan Province, China. Based on morphological characterization and phylogenetic analyses, we introduce this fungus as Microdochium sichuanense sp. nov. Maximum likelihood, and Bayesian analyses of combined genes (LSU, ITS and rpb2) were performed to clarify the phylogenetic affinities of the new species. Microdochium sichuanense is phylogenetically closely related to M. hainanense and morphologically it fits the generic characteristics of Microdochium species in having ostiolate ascomata, peridium cells of textura angularis to textura prismatica, unitunicate, clavate to oblong, 8-spored asci and hyaline, oval to fusiform ascospores. The new species was compared with phylogenetically and morphologically closely related species, and detailed descriptions, micrographs, and phylogenetic trees of the new species are provided.